Exposure to light and darkness and its influence on physiological measures of intensive care unit patients—a systematic literature review. (11th August 2016) - Weiss, B; Spies, C; Piazena, H; Penzel, T; Fietze, I; Luetz, A
Abstract: Sleep-wake patterns are often significantly disturbed in critically ill patients. This disturbance is closely linked to secondary brain dysfunctions in these patients. Sedation not only impairs sleep quality in ICU patients but also has detrimental effects on short- and long-term outcome. In other contexts, light therapy has been proven to be effective in maintaining and resynchronizing circadian rhythmicity in humans. The objective of this systematic review was to analyse studies that investigated the effect of exposure to light or darkness on physiological measures and clinical outcomes of adult ICU patients. Studies were systematically identified by searching electronic bibliographic databases (The Cochrane Central Register of Controlled Trials (CENTRAL, The Cochrane Library, 2002) and MEDLINE via PubMed). The search algorithm identified a total of 156 articles, 10 of which were taken into final review. These 10 selected articles included 3 were monocentric RCTs, five prospective cohort studies, one retrospective cohort study, and one manuscript that included a partial systematic review of the literature. Included trials were published between 2007 and 2015. Five of these studies used multiple intervention approaches while four trials used a single intervention approach. Among all studies, 1, 278 patients were analysed (489 prospectively). There was a high heterogeneity among the studies in terms of applied intervention and outcome measures. The most frequent methodological limitations were a lack of precise definitions regarding the illuminance and the light spectrum utilised. The analyses indicate that further studies including clearly defined interventions with objective outcome measures, as these are currently lacking, would add significant knowledge to this new field of research.